Variability of some isolates of Prunus necrotic ringspot virus and Prune dwarf virus infecting sour and sweet cherry in Ukraine - Liliia PAVLIUK; Kateryna UDOVYCHENKO; Iryna RIABA; Mykola BUBLYK (Acta Agriculturae Slovenica)
Prunus necrotic ringspot virus (PNRSV) and Prune dwarf virus (PDV) are the most common pathogens in stone crop orchards. These diseases are easily transmitted with pollen and hence rapidly spread in orchards leading to stunting of trees, their increased susceptibility to abiotic stress factors and, eventually, to significant yield losses. In Ukraine, only monitoring studies on the spread of these viruses were conducted until now. However, phylogenetic comparison of Ukrainian isolates was lacking. In this work, total RNA was isolated from plant samples tested positive for PNRSV and PDV by ELISA. The part of viral CP gene sequences were amplified and sequenced with their subsequent phylogenetic analysis. It was determined that PNRSV isolates from Ukraine analyzed in this study belong to different groups – PV-96 (MT828889) and PV-32 (MT892676) with a maximum identity level of 100 % with known isolates from NCBI GenBank. PDV isolates (MT828888 and MT828887) showed high identity with each other (99.6 %), and Slovakian isolate from sweet cherry was shown as the most related to them with identity of 95.3 %.